Some aspects of a two-layer, shallow water non-linear internal wave, in a rectangular tank - Molines, J. M. (Revista Técnica da Faculdade de Engenharia da de Zulia, 1970)
Equations of motion are developped in the general frame of the shallow water theory and for t he case of a two-dimentional two-layer irrotational fluid. The solution is expressed as a cnoidal internal wave and solitary wave is found as a limit. Laboratory experiments were carried out in a two-dimensional oscillating tank, to test the validity of the theoretical solution.